2011
DOI: 10.3354/cr01009
|View full text |Cite
|
Sign up to set email alerts
|

Floristic mapping data as a proxy for the mean urban heat island

Abstract: Assessment of spatial variability in the long-term urban heat island (UHI) is severely restricted by coverage and availability of measurements. This also limits the opportunities to analyse its relation to surface characteristics. In this study we therefore introduce a new proxy dataset derived from floristic mapping. The basic assumption is that the species composition in an area reflects climatologic conditions of a certain time period. Ellenberg indicator values for temperature (EITs) were processed to summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…This leads to well-known urban effects such as the urban heat island [77][78][79], urban impacts on precipitation [80][81][82] and urban air pollution [83]. In urban areas and metropolitan regions in Europe, air pollution is mainly caused by traffic, with a high share of heavy commercial vehicles [84].…”
Section: Urban Impacts On Environmental Variablesmentioning
confidence: 99%
“…This leads to well-known urban effects such as the urban heat island [77][78][79], urban impacts on precipitation [80][81][82] and urban air pollution [83]. In urban areas and metropolitan regions in Europe, air pollution is mainly caused by traffic, with a high share of heavy commercial vehicles [84].…”
Section: Urban Impacts On Environmental Variablesmentioning
confidence: 99%
“…Recent studies focus on sealed soils in urban areas (a detailed review can be found in Scalenghe and Marsan 2009), infiltration processes, and the urban water management system (e.g., Mohrlok et al 2008;Barron et al 2013), or report on urban soil's physical, chemical, and biological properties (Scharenbroch et al 2005). Besides urban pedosphere, also its adjacent spheres like atmosphere and biosphere have special urban anthropogenic properties (Endlicher 2011), contributing to the multifactorial and diverse impacts on urban soils as well (e.g., shown for flora in Bechtel and Schmidt 2011). Yet, specific studies on urban soil water dynamics are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…This results in UHI-like effects at night due to the advection of warm air from the adjacent water bodies ). The water-and urban-fabric-induced reduced night-time cooling are additive and also affect the occurrence of plant species (Bechtel and Schmidt 2011). For large water bodies, such as the River Elbe downstream of Hamburg's harbour the water bodies might cause a river breeze that affects temperatures a few 1000 m off the river, as Teichert (2013) found for a calm meteorological situation in summer simulated with METRAS.…”
Section: Temperature and Humiditymentioning
confidence: 94%